Imaging After Nellix Endovascular Aneurysm Sealing: A Consensus Document. (February 2016) - Holden, Andrew; Savlovskis, Janis; Winterbottom, Andrew; van den Ham, Leo H.; Hill, Andrew; Krievins, Dainis; Hayes, Paul D.; Reijnen, Michel M. P. J.; Böckler, Dittmar; de Vries, Jean-Paul P. M.; Carpenter, Jeffrey P.; Thompson, Matt M.
Endovascular aneurysm sealing (EVAS) using the Nellix system is a new and different method of abdominal aortic aneurysm repair. Normal postoperative imaging has unique appearances that change with time; complications also have different and specific appearances. This consensus document on the imaging findings after Nellix EVAS is based on the collective experience of the sites involved in the Nellix EVAS Global Forward Registry and the US Investigational Device Exemption Trial. The normal findings on computed tomography (CT), duplex ultrasound, magnetic resonance imaging, and plain radiography are described. With time, endobag appearances change on CT due to contrast migration to the margins of the hydrogel polymer within the endobag. Air within the endobag also has unique appearances that change over time. Among the complications after Nellix EVAS, type I endoleak usually presents as a curvilinear area of flow between the endobag and aortic wall, while type II endoleak is typically small and usually occurs where an aortic branch artery lies adjacent to an irregular aortic blood lumen that is not completely filled by the endobag. Procedural aortic injury is an uncommon but important complication that occurs as a result of overfilling of the endobags during Nellix EVAS. The optimum imaging surveillance algorithm after Nellix EVAS has yet to be defined but is largely CT-based, especially in the first year postprocedure. However, duplex ultrasound also appears to be a sensitive modality in identifying normal appearances and complications.